Pengaru Kompensasi, Budaya Organisasi, dan Motivasi Kinerja Karyawan: Studi Kasus PT SAMUDRA TANPA BATAS - Yasir, Akhdan (Faculty of Economics and Business, 2025)
This study aims to explain the effect of compensation, organizational culture, and motivation on employee performance at PT Samudra Tanpa Batas. Utilizing a quantitative research approach, the study's population included all employees of PT Samudra Tanpa Batas, with a saturated sample of 50 respondents. Data were collected through questionnaires, observations, and interviews, then processed using multiple linear regression analysis with SPSS 29 Software. The findings indicate that compensation did not have a partial effect on employee performance, and motivation also did not have a partial effect on employee performance. However, organizational culture showed a partial effect on employee performance. Collectively, compensation, organizational culture, and motivation have a stimulant effect on employee performance.